The persistency evaluation of Czech varieties of Red (Trifolium pratense L.) and Alsike Clover (Trifolium hybridum L.) - Stanislav Hejduk (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2006)
Red clover is the most important forage legume in the Czech Republic. It is an unassuming species to climatic and soil condition, is suitable for mixtures with grasses and it is above other grassland species in forage quality. The most serious problem of red clover in grasslands is its lack of persistency (2–4 years). Considering of red clover growing area on arable land decrease and area of permanent grasslands increases, becomes persistency of varieties important attribute. The persistency of all Czech varieties was evaluated on the basis of dominance proportion investigation after 3 winters. Assessed varieties were established in mixture with grasses (60:40%). Significantly most persistent varieties were Amos 4n (24.5%), Dolina 4n (20.25 %) and Radegast 4n (19.25%). Varieties of Alsike clover were not significantly different from varieties of red clover.